2013
DOI: 10.7205/milmed-d-12-00347
|View full text |Cite
|
Sign up to set email alerts
|

Developing Physical Capability Standards That are Predictive of Success on Special Forces Selection Courses

Abstract: This study aimed to develop minimum standards for physical capability assessments (vertical jump, sit and reach, push-ups, seven-stage sit-ups, heaves, agility, 20-m shuttle run, loaded 5-km pack march, and 400-m swim) that candidates must pass before they can commence Australian Army Special Forces (SF) selection courses. Soldiers (Part A: n = 104; Part B: n = 92) completed the physical capability assessments before commencing a SF selection course. At the beginning of these selection courses, participants at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 10 publications
9
45
1
Order By: Relevance
“…The 20 m PSRT was selected as the outcome measure for several reasons. Firstly, this is a test commonly employed in tactical occupations (3,10,20). Secondly, 20 m PSRT scores are the current standard unit of measure by this police academy.…”
Section: Methodsmentioning
confidence: 99%
“…The 20 m PSRT was selected as the outcome measure for several reasons. Firstly, this is a test commonly employed in tactical occupations (3,10,20). Secondly, 20 m PSRT scores are the current standard unit of measure by this police academy.…”
Section: Methodsmentioning
confidence: 99%
“…The small sample size available is a clear limitation of this study. It should be noted, however, that data from the entire selection course were used and other studies in this area have also used smaller sample sizes, given the unique nature of this occupation [ 1 , 5 ]. The measure of body composition would have been ideal, however given the logistical and time burden to perform these measurements, it was not feasible to conduct this measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the selection courses for entry into these units are physiologically and psychologically demanding, designed to match the operational requirement of this job role [ 5 ]. Reported failure rates in military special forces range from 45 to 55% in the US [ 6 ] to 30 to 82% in Australia [ 5 ] and 69% in Specialist Police in Australia [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research that sought to establish normative data for military personnel in the U.S. used a single leg vertical jump, a 6-m timed hop and a triple hop and found that males performed better in power than females and those who were under 30 years old performed better on power than those over 30 years old [124]. A vertical jump test was also employed in a study on the Australian army special forces for developing the minimum standards for a pre-selection physical capability assessment [125]. A review of the methods that could replace or supplement the current test among U.S. Navy personnel found that the standing long jump was highly correlated and could be used as part of the navy’s physical readiness test [126].…”
Section: Physical Fitnessmentioning
confidence: 99%